Targeting Cytosolic Nucleic Acid-Sensing Pathways for Cancer Immunotherapies - Iurescia, Sandra; Fioretti, Daniela; Rinaldi, Monica (Frontiers in Immunology, 2018)
The innate immune system provides the first line of defense against pathogen infection though also influences pathways involved in cancer immunosurveillance. The innate immune system relies on a limited set of germ line-encoded sensors termed pattern recognition receptors (PRRs), signaling proteins and immune response factors. Cytosolic receptors mediate recognition of danger damage-associated molecular patterns (DAMPs) signals. Once activated, these sensors trigger multiple signaling cascades, converging on the production of type I interferons and proinflammatory cytokines. Recent studies revealed that PRRs respond to nucleic acids released by dying, damaged, cancer cells, as danger DAMPs signals, and presence of signaling proteins across cancer types suggests that these signaling mechanisms may be involved in cancer biology. DAMPs play important roles in shaping adaptive immune responses through the activation of innate immune cells and immunological response to danger DAMPs signals is crucial for the host response to cancer and tumor rejection. Furthermore, PRRs mediate the response to nucleic acids in several vaccination strategies, including DNA immunization. As route of double-strand DNA intracellular entry, DNA immunization leads to expression of key components of cytosolic nucleic acid-sensing pathways. The involvement of nucleic acid-sensing mechanisms in the anti-tumor response makes these pathways attractive drug targets. Natural and synthetic agonists of nucleic acid-sensing pathways can trigger cell death in malignant cells, recruit immune cells such as DCs, CD8+ T cells and NK cells into the tumor microenvironment and are being explored as promising adjuvants in cancer immunotherapies. In this minireview we discuss how cGAS–STING and RIG-I–MAVS pathways have been targeted for cancer treatment in preclinical translational researches. In addition, we present a targeted selection of recent clinical trials employing agonists of cytosolic nucleic acid-sensing pathways showing how these pathways are currently being targeted for clinical application in oncology.